The Oxidation of 2-(2-Methoxyethoxy)ethanol and 2-(2-Ethoxyethoxy)ethanol by Ditelluratocuprate(III): A Kinetic and Mechanistic Study - Jin-huan Shan; Yi Li; Shu-ying Huo; Cai-hong Yin (Journal of Chemistry)
The oxidation of 2-(2-methoxyethoxy)ethanol (MEE) and 2-(2-ethoxyethoxy)ethanol (EEE) by ditelluratocuprate(III) (DTC) had been studied spectrophotometrically in alkaline medium. The reaction between and showed first-order dependence in DTC and fractional order in MEE and EEE. The rate constant of the pseudo-first-order reaction decreased with an increase of [TeO4  2−], whereas adding [OH−] enhanced the constant. In addition, the reaction had a negative salt effect. The rate of EEE was higher than that of MEE. A suitable assumption involving preequilibriums before the rate-controlling step and a free radical mechanism was proposed, based on the kinetic data. Activation parameters and the rate constant of the rate-determining step were calculated.